Hydrothermal liquefaction of microalgae using Fe3O4 nanostructures as efficient catalyst for the production of bio-oil: Optimization of reaction parameters by response surface methodology. (December 2019) - Kandasamy, Sabariswaran; Zhang, Bo; He, Zhixia; Chen, Haitao; Feng, Huan; Wang, Qian; Wang, Bin; Bhuvanendran, Narayanamoorthy; Esakkimuthu, Sivakumar; Ashokkumar, Veeramuthu; Krishnamoorthi, M.
Abstract: The aim of the present work was focused on optimizing the hydrothermal liquefaction (HTL) of Spirulina platensis catalyzed by Fe3 O4 nanostructures to enhance the bio-oil yield and quality of bio-oil using response surface methodology (RSM). The structural morphology and crystalline nature of the synthesized catalyst was determined using a scanning electron microscope (SEM), high resolution transmission electron microscopy (HR-TEM) and X-ray powder diffraction (XRD). Three of the vital reaction parameters such as temperature, holding time and catalyst dosage were optimized through central composite design. A maximum bio-oil yield of 32.33% was observed for the high temperature at 320 °C, 0.75 g of catalyst dosage and 37 min of resident time. The maximum conversion was found at a lower temperature of 272 °C, the bio-oil yield of 27.66% was obtained with 0.45 g of catalyst dosage and 24 min of holding time which is an energy efficient optimum condition. The maximum bio-oil yield was influenced at a lower temperature due to the high catalytic activity. While compared to higher temperatures were not much influence was observed. It clearly states that the catalyst dosage playing a critical role in the lower temperature HTL reaction. GC-MS and FT-IR analysis of the produced bio-oil exhibits significant characteristics for biofuel applications. The Fe3 O4 catalyst was recyclable for up to eight repeated cycles and constant bio-oil yield for the last four cycles. It shows the excellent reproduction ability towards HTL of Spirulina sp . Highlights: HTL of microalgae catalyzed by Fe3 O4 and fitted by RSM. Fe3 O4 synthesized by one-step precipitation method without any stabilizing agent. Effect of temperature, catalyst dosage and resident time on HTL was studied. The optimum bio-oil yield of 27.66% for Fe3 O4 catalyzed HTL at 272 °C. GC-MS results revealed good quality of bio-oil for biofuel applications.